The streetlight effect in type 1 diabetes - Battaglia, Manuela; Atkinson, Mark A (Diabetes (New York, N.Y.), 2015)
In the nearly 100 years since the discovery of therapeutic insulin, significant research efforts have been directed at finding the underlying cause of type 1 diabetes (T1D) and developing a "cure" for the disease. While progress has clearly been made toward each of these goals, neither vision has been fulfilled. With increasing pressure from both public and private funders of diabetes research, growing impatience of those with T1D at the lack of practical discoveries, increased competition for research funds, uncertainties on the reproducibility of published scientific data, and questions regarding the value of animal models, the current research environment has become extraordinarily difficult to traverse from the perspective of investigators. As a result, there is an increasing pressure toward performance of what might be considered "safe" research, where the aim is to affirm existing dogmas rather than to pioneer efforts involving unconventional thought. Psychologists refer to this practice as "observational bias" while cartoonists label the process the "streetlight effect." In this Perspective, we consider notions in T1D research that should be subject to bold question and provide additional concepts, many somewhat orphan to research efforts, whose investigation could lead to a means for truly identifying the cause of and a cure for T1D.